(untitled) (Sinología hispánica. China Studies Review, 2021)
Language service in the sanitary crisis: theories and practices in Chinese context technological activities, into its definition. In the fight against the COVID-19 crisis, under the framework of “emergency linguistics”, Chinese linguists, digital developers and university students carried out language supports in order to solve the communication problems between authorities, health workers, citizens and foreigners living in China. Specifically, they published manuals of Hubei dialects and instructions in foreign languages and in basic Chinese on how to protect oneself in the pandemic; moreover, they collected information for the needy communities and cared about the international students’ psychological state. On the other hand, machine and human translation platforms and mobile applications were created. However, we notice an inconsistency between the theoretical approaches to the term “language service” and the practices in the pandemic, which is why we suggest caution in the development of new terms and in the integration of theories and practices.